A caring leadership model in nursing: A grounded theory approach. (26th March 2022) - Zhang, Fengjian; Peng, Xiao; Huang, Lei; Liu, Yilan; Xu, Juan; He, Jiao; Guan, Chunyan; Chang, Hongwei; Chen, Yuqin
Abstract: Aim: This study aimed to develop a theoretical model of caring leadership in nursing. Background: Nurse leader's role plays an integral part in complex health care institutions. As a common feature of leaders, leaders' caring leadership can positively influence the stakeholders in health care institutions. Still, little is known about caring leadership in nursing, especially in the Chinese cultural background. Methods: Grounded theory was used to develop the theoretical model of caring leadership. Both semi‐structured interviews and open‐ended questionnaire surveys were used to collect data for constructing the theory model. Ten nurse leaders and 11 nurse staff were recruited for an interview, and 168 nurse leaders and 286 nurses were recruited for an open‐ended questionnaire survey. Results: A theoretical model of caring leadership was developed using five core attributions: benevolent to others, appreciate the uniqueness, facilitate self‐actualization, maintain mutual benefit and motivate with charisma. Caring leadership in nurse leaders works through the caring and leading process, resulting in nurses' well‐being, patients' healing and organisational excellence. Conclusion: A caring leadership model was developed through grounded theory, revealing Chinese nurses' perspectives on caring leadership in Chinese cultural background. According to the model, the concept of caring leadership has been further explained, and it makes contributions to the measurement and leaders' practice in health care institutions. Implications for Nursing Management: This caring leadership model developed in our study provides a new perspective and understanding of caring and leadership for nurse leaders. Nurse leaders need to strengthen their responsibilities and personal qualities while caring for nurse staff to improve leadership efficacy based on the theoretical model. And caring leadership can help nurse leaders to balance the interests of stakeholders, leading to positive consequences for nurse staff, patients and health care organisations.